Meningkatkan Kinerja Pemasaran: dengan Kreativitas Strategi - Widodo, Widodo (International Research Journal of Business Studies, 2008)
This study explores new variables that support strategic creativity in marketing according to Menon et al. (1999). Those variables are: reward, individual performance, and team work effect. Therefore, there are four hypotheses that are tested in this research. Firstly, the higher the strategic creativity, the higher the marketing peformance. Secondly, the higher the reward, the higher the strategic creativity. Thirdly, the higher the individual performance, the higher the strategic creativity. And lastly, the higher the team perfomance, the higher the strategic creativity. Multiple regression analysis is used to test the hypotheses using inputs from fifty respondens. The result shows that those hypotheses can be accepted. Managerial implications correspond to the result are discussed at the end of this article.